An Efficient Asymmetric Inverter Design for PV Applications for Harmonics and Power Loss Mitigation - Lingaswamy Kandadi; Jebaseelan S.D. Sundarsingh (E3S Web of Conferences)
The electricity industry faces major problems due to the ubiquitous availability of fossil fuels and their rising consumption. One option is to use photovoltaic (PV) modules, which convert sunlight into electricity—at first, in the form of direct current (DC). But changing it to alternating current (AC) is essential for powering AC loads. Problems with electromagnetic interference (EMI) and harmonic distortion are common with traditional inverters. Because of this, multi-level inverters (MLIs) have been developed to reduce harmonic content. But current MLIs are often symmetrical and need an increasing number of switching devices as output levels rise, rendering them unsuitable for PV applications caused by environmental variations. In order to overcome these restrictions, this research suggests an asymmetric inverter that uses eight power switches to provide a fifteen-level output from asymmetrical direct current sources. Suggested topology's decreased amount of switches improves system efficiency by minimizing size and switching losses. To further enhance the inverter's output voltage profile and efficiency, Sinusoidal Pulse Width Modulation (SHEPWM) is used to efficiently reduce particular harmonics. In order to more effectively remove complex harmonics, the switching angles of the suggested MLI are adjusted using a Particle Swarm Optimization (PSO).